Costing of workplace accident in Singapore : the prevalence, incidence and the projection of workplace safety and health. - Lim, Wei Jian. (2009)
In line with the government’s target to reduce the number of work-related fatalities to 1.8 per 100,000 workers by 2018, this paper seeks to look into the issue of local workplace safety and health (WSH) from the angle of accident costing. Scrutinizing this issue from the point of view of commercial firms which seek to optimize profit as well as to maximize the employees’ welfare, the group finds that the cost of workplace accident in Singapore might be underestimated. Managers need a higher motivation to strive for better WSH standard. A better costing method not only helps to enhance the capabilities of companies to assess the effectiveness of ergonomic investments, it also improves working conditions indirectly. With reference to the COWA initiatives in the United States of America (US) and the United Kingdom (UK), the group examines the practice of COWA in Singapore and made comparison. The group also met with personnel from the Workplace Safety and Health Council (WSHC) to find out more about the on-going project of Accident Cost Calculator. The later part of this paper presents a case study on a fatal accident involving several workers from a construction company. The costs of the accident were assessed and compared with the accounting costs recorded by the company of interest. Finally, the group explores some issues related to the future progress of COWA in Singapore, as Singapore works towards to becoming a centre of excellence for WSH.